The impact of foreign direct investment on the economy in developing countries - lukman hakim; Irham Fahmi (Institute of Computer Science (IOCS), 2023)
Foreign Direct Investment (FDI) is a critical factor in shaping the economic development of developing countries. This study conducts a systematic literature review using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) diagram to comprehensively assess the multifaceted impact of FDI on developing economies. The primary objective is to synthesize existing research and provide insights into the intricate relationship between FDI inflows and economic growth, industrialization, technological progress, job creation, and trade dynamics in these countries. Method: In April 2023, a rigorous search in the Scopus database yielded 93 relevant articles after filtering based on language (English) and time (2018-2023). Further refinement narrowed the focus to 61 publications on